Arduino-based Spectrometer Design for Measurement of Liquid Absorbance - Yohandri, Yohandri; Rahmawati, Diah (Journal of Experimental and Applied Physics, 2023)
The Spectrometer is an important common analytical equipment that measures the concentration of analytes via their absorbance of light at specific wavelengths. However, many laboratories with limited resources cannot afford such equipment. A Spectrometer utilizes the wavelength of the electromagnetic spectrum. The main component of the spectrometer is the sensor detector. The BH1750 sensor is used to detect the absorbance of the sample after being irradiation with a Light Emitting Diode Red Green Blue (LED RGB). If the RGB light irradiated the sample, the sensor will read the output value according to the Arduino Programming. This study used Congo red samples with various concentrations of 20, 30, 40, 50, and 60 ppm. the tool can be developed at low cost and the performance of the tool is highly satisfactory in terms of accuracy and precision.